Subterranean nesting behaviour in response to soil moisture conditions in the southern ant, Monomorium antarcticum Smith (Hymenoptera: Formicidae). Issue 1 (2nd January 2020) - Lamb, S. D.; McCombe, G. G. I.; Lawrence, E.; Macwan, R.; Mayer, T.; Jandt, J. M.
ABSTRACT: The New Zealand endemic southern ant ( Monomorium antarcticum ) excavates subterranean nests in various soil types, with brood distributed throughout excavated cavities connected by tunnels. Because cavities are often constructed near the soil surface, variation in rainfall patterns will affect soil moisture, and potentially lead to regular flooding of cavities. We examined how M. antarcticum make colony emigration decisions as soil moisture changes over time, and investigated how colonies manage brood underground during simulated rainfall events. We show that colonies will emigrate to wetter soil and excavate a new nest when their environment becomes too dry. After we add water to the surface of the nest (i.e. simulate rainfall), workers transport brood from cavities into tunnels, and move them back into the cavities as soon as the 'rain' stops. Workers tend to prioritise moving brood from cavities with higher densities of brood, regardless of the depth of the cavity from the soil surface. We discuss how the ability to emigrate in response to changes in soil environment, and to effectively respond to unpredictable rainfall/flooding events, can help us understand how this species persists in a wide-range of habitat types.